Dynamics modeling of traffic-related exhaust aerosols - Sheludchenko, Lesya (Lviv Politechnic Publishing House, 2017)
The results of analytical researches of migration processes and turbulent diffusion of exhaust aerosols, produced by traffic flows within reserve technical lanes of highways are given. It is concluded that rotors, determined as some areas of the rotary motion of an aerosol, are always formed within the diffusion divergence field of turbulent flows of exhaust aerosol.
Keywords: Exhaust cloud; aerosol; diffusion; migration